The effect of two methods of feedback on the writing accuracy of low-proficiency learners : Coding vs. underlining - Waleed Nasr Elbadawy; Amira Agameya; Randa Anwar (Cairo : Waleed Nasr Elbadawy, 2019)
The present study investigated the effectiveness of two indirect types of feedback, coding and underlining, on the development of the writing of lowproficiency learners. The study, additionally, examined the impact of the two feedback types on the improvement of five linguistic categories, namely, subject-verb agreement, singular and plural, the use of tenses, adjectives and nouns. It involved a total of 27 participants. A quasi-experimental design was used with each group receiving one type of feedback. For both groups a pretest and a post-test were administered to track the progress in whole groups and for individual learners. Both quantitative and qualitative designs were conducted to measure the development in both groups and in the performance of each individual student. To get the results, a t-test was administered to examine whether there was a statistically significant difference in the performance of both groups before and after the treatment. The results of the study show that there was a statistically significant difference in the performance of participants within each group. Both techniques, besides, helped learners improve their performance in the use of most of the five linguistic categories. The subject verb agreement was the most developed linguistic type among the five linguistic categories focused upon in the study
Thesis (M.A.) - Cairo University - Faculty of Arts - Department of English
Issued also as CD
Keywords: Indirect feedback; Low-proficiency learners; Writing feedback